Evaluation of a puppet video on physical activity as a diabetic education material for older children - Glorioso, Idelia G.; Narciso, Zenaida V.; Avilla, Jerlyn D.; Ducay, Apple Joy D.; Capanzana, Mario V. (2018)
A puppet video on physical activity was developed based on the No. 10 Message of the 2000 Nutritional Guidelines for Filipinos, with emphasis on the prevention of diabetes through regular physical activity. Puppets and videos are among creative educational tools to promote health and nutrition concepts. The study aimed to evaluate a puppet video on physical activity based on improvement of nutrition knowledge of schoolchildren after exposure to the video. It also examined the determinants that contributed to the improvement of nutrition knowledge scores of these children. The video was evaluated among 1857 selected Grade 6, first, second, third, and fourth year high school students from public schools in Sep 2015 at six study sites in the Philippines. Study participants aged 10?17 years old and above were distributed among age brackets of 10?12 years old, 13?14 years old, 15?16 years old, and 17 years old and above. The average age of study participants was 13.5 years old. The test-retest technique was conducted to gather data from the participants who answered knowledge test questionnaire before and after watching puppet video. Findings indicated that the puppet video was effective in improving knowledge scores before and after video showing based on significant T-test results. Analysis of variance revealed gender, age, grade/year level, and geographical location as significant determinants of the improvement of knowledge scores of the children. Item analysis showed significant increases in mean scores of 4 out of 5 questions/concepts before and after exposure to the video. The four concepts included: (a) diabetes as a result of lack of exercise, (b) lifestyle diseases other than diabetes resulting from lack of exercise, (c) avoiding overweight as a means to prevent diabetes, and (d) duration and frequency of exercise. The study recommended the following: (a) starting diabetic education among older children considering the increasing prevalence of obesity and diabetes among them; (b) integration of the use of this video in class sessions of the children; and (c) using the video in other venues such as pediatric clinics, play areas, malls, and other places where children congregate. (Author's abstract)